Beneficial Effects of Coculturing Synovial Derived Mesenchymal Stem Cells with Meniscus Fibrochondrocytes Are Mediated by Fibroblast Growth Factor 1: Increased Proliferation and Collagen Synthesis - Xuanhe Song; Yaoping Xie; Yang Liu; Ming Shao; Wenbo Wang (Stem Cells International)
Meniscus reconstruction is in great need for orthopedic surgeons. Meniscal fibrochondrocytes transplantation was proposed to regenerate functional meniscus, with limited donor supply. We hypothesized that coculture of synovial mesenchymal stem cells (SSC) with meniscal fibrochondrocytes (me-CH) can support matrix production of me-CH, thus reducing the number of me-CH needed for meniscus reconstruction. A pellet coculture system of human SSC and me-CH was used in this study. Enhanced glycosaminoglycans (GAG) in coculture pellets were demonstrated by Alcian blue staining and GAG quantification, when compared to monoculture. More collagen synthesis was shown in coculture pellets by hydroxyproline assay. Increased proliferation of me-CH was observed in coculture. Data from BrdU staining and ELISA demonstrated that conditioned medium of SSCs enhanced the proliferation and collagen synthesis of me-CH, and this effect was blocked by neutralizing antibody against fibroblast growth factor 1 (FGF1). Western blot showed that conditioned medium of SSCs can activate mitogen-activated protein kinase (MAPK) signaling pathways by increasing the phosphorylation of mitogen-activated regulated protein kinase 1/2 (MEK) and extracellular-signal-regulated kinases 1/2 (ERK). Overall, this study provided evidence that synovial MSCs can support proliferation and collagen synthesis of fibrochondrocytes, by secreting FGF1. Coimplantation of SSC and me-CH could be a useful strategy for reconstructing meniscus.